PENGARUH PERSON ORGANIZATIONAL-FIT DAN KEPUASAN KERJA TERHADAP TURNOVER INTENTION YANG DIMEDIASI OLEH KOMITMEN ORGANISASI PT. PERTAMINA BANDA ACEH - Zidny Ilma Setiawan; Nurlina Nurlina (Departemen Manajemen, 2022)
This study aims to measure the effect of Person Organizational-fit and Job Satisfaction on Turnover Intetion Mediated by Organizational Commitment at PT.Pertamina Banda Aceh. The sample consists of 70 employees of PT.Pertamina Banda Aceh. The sampling technique used was non-probability sampling method and the type of sampling used was total sampling. Data collection equipment used in this study was questionnaire. Hierarchical Linear Modeling (HLM) is used as an analytical method to determine the variables involved. The results of the analysis show that Person Organizational-fit and job satisfaction have a significant effect on Organizational commitment and Turnover Intetio, Organizational commitment has a significant effect on Turnover Intetion, and Organizational commitment partially mediates the influence between Person Organizational-fit and Turnover Intetion, as well as the relationship between job satisfaction and Turnover Intetion.